Mucuna yadaviana sp. nov. (Leguminosae: Papilionoideae) from the Andaman Islands, India - Swaroopsingh, Gaikwad; Pramod, Lawand; Rajaram, Gurav (Phytotaxa, 2018)
A new species Mucuna yadaviana is described and illustrated. It grows in the tropical evergreen forests of the Andaman Islands of India. It resembles Mucuna imbricata in having lamellate and winged pods, but differs by a set of characters relating to habit, leaf and seeds.